Development of bioactive edible coatings enriched with extracts of celery and banana inflorescence for the preservation of persimmons - de Oliveira, Izamara; da Silveira, Tayse F F; Dos Santos Garcia, Vitor Augusto [UNESP]; Veiga-Santos, Pricila [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Lima, Laíres A; Santos-Buelga, Celestino; Barros, Lillian; Heleno, Sandrina A; Carocho, Márcio (Elsevier, 2025)
Edible coatings enriched with bioactive compounds have emerged as promising alternatives to synthetic preservatives, aligning with sustainability goals and offering solutions for the conservation of perishable fruits. This study aimed to develop and evaluate the efficacy of edible coatings formulated with celery (Apium graveolens L.) and banana inflorescence (Musa acuminata var. "Dwarf Cavendish") extracts, known for their antioxidant properties, in extending the shelf life of persimmons (Diospyros kaki L. var. Giombo). The extraction of phenolic compounds and flavonoids from both botanical sources was optimized using Response Surface Methodology (RSM), and the extracts were incorporated into agar-based edible coatings. Physicochemical parameters such as color (L*, a*, b*), pH, total phenolics, antioxidant activity (DPPH, FRAP), and total carotenoids were analyzed throughout storage at both refrigerated and room temperatures. The coatings exhibited moderate but significant effects on persimmon preservation, particularly in maintaining lightness (L*). Celery extract-based coatings showed 61.0 ± 2.1 at day 10 under refrigeration, compared to 55.0 ± 3.4 in banana inflorescence formulations. Over the storage period, total phenolics in coated samples degraded at a slower rate (0.3 ± 0.2 mg GAE/g in refrigerated conditions), while the antioxidant activity remained higher (DPPH EC50 = 80 ± 12 μg/mL for celery coatings at day 10). Color degradation was evident across all treatments, but coatings with celery extract were more effective in reducing changes in b (yellow-blue coordinate)**, maintaining a b value of 51 ± 6 at day 10, whereas uncoated samples decreased to 47 ± 10. These findings suggest that while the tested coatings provide some level of preservation, further optimization is required to enhance their efficacy, particularly in improving barrier properties and bioactive compound stability. Future research should focus on refining formulations by incorporating additional stabilizers and optimizing temperature conditions to enhance the preservation and safety aspects of coated fruits, ensuring their viability for commercial applications in the food industry.